Wyniki badań i nadzorów archeologicznych przeprowadzonych na ulicy Kościuszki w Rzeszowie w 2018 roku - Gorazd-Dziuban, Paulina; Jabłkowski, Michał; Kocańda, Paweł (Muzeum Okręgowe w Rzeszowie, 2021)
The article focuses on the results of archaeological works and watching briefs that were conducted at Kościuszko Street in Rzeszów in 2018. In the course of research the remains of the wooden lining of the street were uncovered, which were associated with the street reconstruction and functioning until the Austrian times. Additionally, the thesis about a much shorter range of Kościuszko Street and the distinctiveness of the parish church as an additional point in the urban defence system was confirmed. The presented text deals with describing each of the excavation trench and summarizing the results of an archaeological watching brief.

In 2018, the Foundation for Archaeological Centre in Rzeszów conducted archaeological research preceding investment works at Kościuszko Street in Rzeszów. This street, considered one of the oldest, originally connected the market square with the parish church and 3 Maja Street (formerly Pańska). Based on the conducted research, it was possible to determine the original scope of this route and confirm the thesis that the town and the parish church were located on two hills, separated by a small gorge, running roughly at the intersection of Kościuszko Street from Grunwaldzka Street. In addition, the stratigraphic system and the greater number of levels of wooden lining of the street that were found in the archaeological trenches led to the assumption that the area was coming down towards the east. What is more, visible traces of replacing wooden parts in the exploited street, a large number of movable artefacts and animal bones indicate that the street leading to the parish church was an important element in the urban layout of Rzeszów from the Modern Period. Moreover, the conducted research and watching briefs also allowed us to confirm how the discussed street ran, what material was used for its construction and what elements appeared in its course. In addition, it was also possible to confirm partially that the parish cemetery had a wider scope than is visible in the preserved iconographic sources. The conducted research together with the obtained archaeological material have become a valuable source of information about the history of Rzeszów and its inhabitants.
Results of archaeological research and watching briefs carried out at Kościuszko Street in Rzeszów in 2018
Keywords: urban archaeology; street lining; parish cemetery; modern city; Rzeszów; urban layout